2015
DOI: 10.1016/j.bbrc.2015.02.128
|View full text |Cite
|
Sign up to set email alerts
|

Chloride concentrations in human hepatic cytosol and mitochondria are a function of age

Abstract: We recently reported that, in a concentration-dependent manner, chloride protects hepatic glutathione transferase zeta 1 from inactivation by dichloroacetate, an investigational drug used in treating various acquired and congenital metabolic diseases. Despite the importance of chloride ions in normal physiology, and decades of study of chloride transport across membranes, the literature lacks information on chloride concentrations in animal tissues other than blood. In this study we measured chloride concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 20 publications
(31 reference statements)
5
30
0
Order By: Relevance
“…Of note, the non-tumor breast tissue showed higher variability in [Cl − ] between donors than did the non-tumor liver samples. Additionally, both non-tumor and tumor breast tissues had mean Cl − levels that were much higher than the liver samples (Figure 5D), while liver mitochondria had very low [Cl − ], consistent with our previous findings [11]. As a whole, only cytosol from liver tumors had Cl − levels that were different from matched controls.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Of note, the non-tumor breast tissue showed higher variability in [Cl − ] between donors than did the non-tumor liver samples. Additionally, both non-tumor and tumor breast tissues had mean Cl − levels that were much higher than the liver samples (Figure 5D), while liver mitochondria had very low [Cl − ], consistent with our previous findings [11]. As a whole, only cytosol from liver tumors had Cl − levels that were different from matched controls.…”
Section: Resultssupporting
confidence: 90%
“…chloride concentration ([Cl − ]) was 0.22 ± 0.07 μmol/mg protein in the cytosol. For reference, we have reported the chloride concentration in normal adult liver cytosol to be approximately 75 mM [11]. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent findings of the effect of chloride on GSTZ11 inactivation could explain these discrepancies. It was found that chloride protects GSTZ11 from inactivation by DCA at physio logically relevant concentrations in the liver [62,63], however the GSTZ11 in liver cytosol of those who were heterozygous for GSTZ1A was less protected from inactivation by physiological (38 mM) chloride than those with other GSTZ1 allelic variants (Table 4). The effect of chloride was such that the GSTZ11 enzymes in livers from individuals with the GSTZ1A variant on one allele were inactivated twice as quickly as those with other haplotypes.…”
Section: Effect Of Chloride On Inactivation Of Gstz1 By Dcamentioning
confidence: 99%